2006
DOI: 10.1089/pho.2006.24.397
|View full text |Cite
|
Sign up to set email alerts
|

Resin Bonding to Dentin Irradiated by High Repetition Rate Er:YAG Laser

Abstract: Objective: This study evaluated the influence of laser irradiation with a high pulse repetition rate on dentin bonding. Background Data: Although resin bonding to erbium:yttrium-aluminium-garnet (Er:YAG) laserirradiated dentin has frequently been investigated, the effects of a high pulse repetition rate have not yet been sufficiently investigated. Methods: Four groups treated under different laser conditions were evaluated in this study: 100 mJ/pulse-10 pulses per second [pps], 50 mJ/pulse-20 pps, 33 mJ/pulse-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…Several factors have been reported to affect the quality of adhesion to lased dentine, including output energy, 12,13 pulse duration, 14,15 focal distance between the tip and the dentine surface, 16 the adhesive system used, 6,17 acid etching, 7,18 and additional priming. 12,19 In order to irradiate uniformly, some studies employed laser irradiation with the dentine specimen fixed to a moving stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors have been reported to affect the quality of adhesion to lased dentine, including output energy, 12,13 pulse duration, 14,15 focal distance between the tip and the dentine surface, 16 the adhesive system used, 6,17 acid etching, 7,18 and additional priming. 12,19 In order to irradiate uniformly, some studies employed laser irradiation with the dentine specimen fixed to a moving stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, they should not be interpreted as adhesive failures, but as the cohesive failures in the laser-damaged dentin which were not impregnated by adhesive resin. 5,14 To achieve sufficient adherence to Er:YAG-lased dentine, it is necessary for the resin monomer to penetrate the laser-affected dentine subsurface to a depth of more than 15 m. 36 In AQP, a larger area of cohesive failure in the adhesive resin was observed than with the other three adhesives. This suggests that the viscosity of the adhesive resin is an important factor in bonding to Er:YAG-lased dentine.…”
Section: B Cmentioning
confidence: 99%
“…[1][2][3][4][5] The Er:YAG laser wavelength of 2.94 lm is coincident to the absorption spectrum of water and OH 2 groups in hydroxyapatite. 1 During irradiation, the incident energy is highly absorbed by water molecules present in dentin crystalline structures and organic components, thus causing sudden heating and water vaporization.…”
Section: Introductionmentioning
confidence: 99%
“…9 Twelve extracted bovine incisors, frozen to maintain freshness, were defrosted and cut at the cervix immediately before specimen preparation. The coronal sides of the cut surfaces were sequentially abraded under a stream of water with SiC paper (180-, 400-, and 600-grit) to prepare flat dentin surfaces.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…Furthermore, in an earlier study, we evaluated the relationship between output energy/pulse frequency and tensile bond strength at the same total energy level, and found that a lower output energy/higher pulse frequency decreased bond strength, possibly due to differences in the mechanical properties of the lasermodified dentin. 9 Investigations of the hardness of the resin-dentin adhesive interface [10][11][12][13] have almost exclusively employed nano-indentation, 10-12 a technique effective for determining the hardness of the submicron hybrid layer on a scale much smaller than that possible with micro-hardness testing. As the subsurface of Er:YAG-laser-irradiated dentin morphologically changed at a depth of 60-190 m, 5,14 this technique may be more effective in analyzing the adhesive interface between resin and Er:YAGlaser-irradiated dentin.…”
Section: Introduction Mmentioning
confidence: 99%